MicroRNA expression in inflammatory bowel disease-associated colorectal cancer - Grillo, Thais Gagno [UNESP] (2021)
MicroRNAs (miRNAs) are non-coding RNA molecules composed of 19–25 nucleotides that regulate gene expression and play a central role in the regulation of several immune-mediated disorders, including inflammatory bowel diseases (IBD). IBD, represented by ulcerative colitis and Crohn’s disease, is characterized by chronic intestinal inflammation associated with an increased risk of colorectal cancer (CRC). CRC is one of the most prevalent tumors in the world, and its main risk factors are obesity, physical inactivity, smoking, alcoholism, advanced age, and some eating habits, in addition to chronic intestinal inflammatory processes and the use of immunosuppressants administered to IBD patients. Recent studies have identified miRNAs associated with an increased risk of developing CRC in this population. The identification of miRNAs involved in this tumorigenic process could be useful to stratify cancer risk development for patients with IBD and to monitor and assess prognosis. Thus, the present review aimed to summarize the role of miRNAs as biomarkers for the diagnosis and prognosis of IBD-associated CRC. In the future, therapies based on miRNA modulation could be used both in clinical practice to achieve remission of the disease and restore the quality of life for patients with IBD, and to identify the patients with IBD at high risk for tumor development.